Long-term predictive modeling of stream condition suggests wide-spread changes within the Chesapeake Bay Watershed, USA - Kelly O. Maloney; Benjamin P. Gressler; Lindsey J. Boyle; Alexander H. Kiser (Hydrobiologia, 2026)
Stream ecosystems worldwide face ongoing degradation, underscoring the urgent need for conservation and restoration. Regional analyses of stream condition have been limited by sparse spatial and temporal data, particularly at long time scales. To address this gap, we used observed data to predict annual biological condition for 360,893 small, nontidal stream reaches in the Chesapeake Bay watershed from 1985 to 2023 (39 years). Predictions were generated using random forest models trained on extensive benthic macroinvertebrate data sets and predictors including natural landscape features, land cover, and climate variables. Four biological metrics were assessed: percent Ephemeroptera, Plecoptera, and Trichoptera excluding Hydropsychidae (EPT-H), percent Ephemeroptera, percent clinger functional group, and the Index of Biological Integrity (IBI). Results revealed degraded biological conditions near Washington, D.C. and Baltimore, Maryland, with declining trends across all metrics in these urbanized areas. Spatial heterogeneity was evident: IBI and clinger percentages increased in many southern streams but declined in northern streams, whereas EPT-H and Ephemeroptera decreased watershed wide except in the Southeastern Plains bioregion. By 2021, watershed wide IBI improvements were predicted for 0.9–1.1% of stream length, falling short of management goals. This study demonstrates the utility of long-term data and machine learning for predicting stream condition, identifying key stressors, and guiding restoration and conservation site selection.

The Effects of Peracetic Acid on Post‐Larvae and Juvenile Pacific White Shrimp ( Litopenaeus vannamei ) and Seven Vibrio Species Isolates at Two Salinities - James T. Tuttle; Timothy J. Bruce; Luke A. Roy; Hisham A. Abdelrahman; Julio C. García; Benjamin H. Beck; David L. Straus; Anita M. Kelly (Journal of Fish Diseases, 2026)
Pacific white shrimp ( Litopenaeus vannamei ) are among the most important aquaculture species but are highly susceptible to Vibrio infections. Novel disease management strategies are necessary. Previous studies have reported that peracetic acid (PAA) is an effective disinfectant, but its application in shrimp aquaculture remains underexplored. This study aimed to determine the median lethal concentration (LC 50 ) of PAA at two life stages of L. vannamei under two salinities and assess its in vitro growth‐inhibitory effects against Vibrio spp. Two groups of 180 juveniles (~5 g) and post‐larvae (maintained at either 4 or 30 g L −1 ) were exposed to six geometrically increasing concentrations of PAA to determine 24‐h LC 50 estimates. Representative juvenile shrimp tissues were histologically assessed. Seven isolates of Vibrio spp. inocula were exposed to PAA and enumerated to determine growth inhibition. The LC 50 estimates varied from 29.09 to 82.40 mg L −1 of PAA. Gill and hepatopancreas tissues were notably damaged at 40.5 and 75 mg L −1 of PAA at 4 and 30 g L −1 , respectively. Growth of all Vibrio spp. was inhibited at the lowest PAA dose tested, that being 0.03125 mg L −1 after 45 min. These findings will help progress the further application of peracetic acid in shrimp aquaculture.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Erratum to “Target sequence capture informs generic delimitation and hybridization in the tribe Lasiopetaleae (Malvaceae)”. [Mol. Phylogenetics Evol. 213 (2025) 108445] - Benjamin M. Anderson; Todd G.B. McLay; Carolyn F. Wilkins; Kelly A. Shepherd (Molecular Phylogenetics and Evolution, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A multiscale seasonal examination of the risk of harm to seabirds from vessels based on co‐occurrence in Alaskan waters - Kelly Kapsar; Benjamin K. Sullender; Katherine J. Kuletz (Conservation Biology, 2026)
Alaska's seascape supports globally significant seabird populations, including vulnerable and threatened species, and hosts economically important commercial fisheries and marine transportation corridors. Seasonal patterns of seabird movements and vessel traffic create a complex landscape of risk, defined as high levels of co‐occurrence (overlap) between seabirds and vessels. Areas of high overlap increase risk of detrimental impacts, such as exposure to artificial light from ships, bycatch, behavioral disturbance, collision, and oil spills. To investigate this risk landscape, we combined satellite‐based automatic identification system (AIS) vessel traffic data (2015–2022) with at‐sea, ship‐based seabird observation data from the North Pacific Pelagic Seabird Database (2006–2022). We used these data to analyze seabird–vessel overlap from June through August (summer) and September through November (fall). Presence of both vessels and birds was highest in summer, presenting a greater overall exposure of seabirds to vessel‐related impacts than in fall. This risk in both seasons was associated with vessel traffic corridors, such as Unimak Pass and the Bering Strait. When only nighttime vessel traffic was considered, risk of disturbance or interaction was higher in fall than in summer north of ∼60° N latitude. Across seasons, regions of highest risk varied by focal taxonomic group. Aethia auklets were most exposed in the northern Bering and Chukchi Seas, and Ardenna shearwaters and northern fulmars ( Fulmarus glacialis ) were most exposed in Unimak Pass. Overall, our findings provide an essential foundation for management decision‐making to reduce risk of vessel‐related injury, contamination, disturbance, displacement, and mortality for marine birds and other wildlife. The heterogeneous distribution of risk across taxa and the persistent spatial concentration of high‐risk areas together require targeted, area‐based mitigation approaches for effective conservation.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Quantifying the carbon footprint of canine breed-specific surgical care in a veterinary referral setting - Rachel L Nixon; Emma Milne; Iwona N Cameron; Tim Nuttall; Benjamin T Blacklock; Kiterie ME Faller; Gudrun Schoeffmann; Tiziana Liuti; John M Ryan; Kelly L Bowlt Blacklock (The Veterinary Journal, 2025)

Effects of fine particulate matter constituents on respiratory and systemic inflammation in elderly adults with and without hypertension: A component-resolved analysis - Bo Peng; Yuanyang Liu; Yiqun Han; Wu Chen; Yifan Xu; Lia Chatzidiakou; Yunfei Fan; Li Yan; Hanbin Zhang; Benjamin Barratt; Yanwen Wang; Teng Wang; et al. (Science of The Total Environment, 2025)

Target sequence capture informs generic delimitation and hybridization in the tribe Lasiopetaleae (Malvaceae) - Benjamin M. Anderson; Todd G.B. McLay; Carolyn F. Wilkins; Kelly A. Shepherd (Molecular Phylogenetics and Evolution, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Geochemical associations of metals in corrosion scales from lead and copper drinking water pipes: Assessing the dissolution and bioaccessibility potentials - Benjamin F. Swaringen; Juliana Matiz; Kelly Milbrandt; David A. Cornwell; George D. Kamenov; Jean-Claude J. Bonzongo (Applied Geochemistry, 2025)

Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

Coinfection of channel catfish ( Ictalurus punctatus ) with virulent Aeromonas hydrophila and Flavobacterium covae exacerbates mortality - Allison L. Wise; Benjamin R. LaFrentz; Anita M. Kelly; Mark R. Liles; Matt J. Griffin; Benjamin H. Beck; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Flavobacterium covae and virulent Aeromonas hydrophila are prevalent bacterial pathogens within the US catfish industry that can cause high mortality in production ponds. An assessment of in vivo bacterial coinfection with virulent A. hydrophila (ML09‐119) and F. covae (ALG‐00‐530) was conducted in juvenile channel catfish ( Ictalurus punctatus ). Catfish were divided into seven treatments: (1) mock control; (2) and (3) high and low doses of virulent A. hydrophila ; (4) and (5) high and low doses of F. covae ; (6) and (7) simultaneous challenge with high and low doses of virulent A. hydrophila and F. covae . In addition to the mortality assessment, anterior kidney and spleen were collected to evaluate immune gene expression, as well as quantify bacterial load by qPCR. At 96 h post‐challenge (hpc), the high dose of virulent A. hydrophila infection (immersed in 2.3 × 10 7 CFU mL −1 ) resulted in cumulative percent mortality (CPM) of 28.3 ± 9.5%, while the high dose of F. covae (immersed in 5.2 × 10 6 CFU mL −1 ) yielded CPM of 23.3 ± 12.9%. When these pathogens were delivered in combination, CPM significantly increased for both the high‐ (98.3 ± 1.36%) and low‐dose combinations (76.7 ± 17.05%) ( p tnfα , il8 , il1b ) demonstrated increased expression levels at 48 hpc. These results demonstrate the additive effects on mortality when these two pathogens are combined. The synthesis of these mortality and health metrics advances our understanding of coinfections of these two important catfish pathogens and will aid fish health diagnosticians and channel catfish producers in developing therapeutants and prevention methods to control bacterial coinfections.

Temporal assessment of fish distribution and abundance in a hypersaline embayment, Hamelin Pool, Shark Bay, Western Australia - Kirsty E. Richards; Kelly L. Campbell; Benjamin J. Saunders; Erica P. Suosaari; Shaun K. Wilson; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2025)

Drivers of Regional Variability in Producer and Consumer Stable Isotope Values (δ13C and δ15N) Within Turtle Grass-Dominated Meadows Across the Northern Gulf of Mexico - Christian Todd Hayes; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Correia; M. Zachary Darnell; Kevin S. Dillon; Bradley T. Furman; Margaret O. Hall; Charles W. Martin; Ashley M. McDonald; Delbert L. Smee; Samantha M. Smith; et al. (Estuaries and Coasts, 2025)

Utilization of Fish Meal and Fish Oil from Smoked Salmon By-Products in Juvenile Striped Bass (Morone saxatilis) Feeds: Growth Performance, Nutritional Composition, and Shelf-Life Assessment of Upcycled Ingredients - Connor Neagle; Michael O. Frinsko; Ryan Kelly; Steven G. Hall; Benjamin J. Reading; Alexander Chouljenko; Greg Bolton; Michael Joseph (Fishes, 2025)
Fish meal (FM) and fish oil (FO) are vital components commonly used in feed formulations. However, their supply, which generally comes from capture fisheries, is being exhausted, necessitating the exploration of sustainable alternatives. In a two-part study, the first part evaluated the FM and FO derived from smoked salmon by-product (SSBP) over a 12-week accelerated shelf-life test, comparing their lipid oxidation, amino acid, and fatty acid profiles to those of commercial whitefish meal and oil. In the second part, the SSBP FM and FO were then included in three experimental feeds at 25%, 50%, and 100% inclusion levels. These feeds were tested on juvenile striped bass (Morone saxatilis) cultured in a recirculating aquaculture system (RAS). The results indicated that the quality of SSBP FM and FO was lower than the commercial product (less amino acids (23.98% vs. 60.30%) and omega-3 fatty acids (9.46% vs. 26.6%), respectively). SSBP FO exhibited high initial peroxide value (21.00 ± 0.00 meq/kg oil), with gradually increasing total oxidation value and p-Anisidine value during storage. Regarding the feeding trial, all fish showed signs of Mycobacterium marinum infection after one month. While there was no significant difference in feed palatability (p > 0.8559), the feed conversion ratio was less efficient for the 100% SSBP feed (1.44 ± 0.14) compared to commercial feed (1.36 ± 0.13), but these differences were not statistically significant. This study suggests that SSBP FM and FO can be used as supplements at lower levels (25% and 50%) without negatively affecting growth, feed efficiency, or survival. Our findings may be useful for enabling beneficial collaborations between smoked salmon processors, feed manufacturers, and striped bass farmers, therefore contributing to sustainability in aquaculture practices.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Institution-Wide Retreats Foster Organizational Learning and Action at a Comprehensive Cancer Center - Benjamin R. Schrank; John A. Fuller; Colleen M. Gallagher; Van K. Morris; Emma B. Holliday; Kelly Merriman; Lynne Nguyen; Lou Weaver; Kelly Nelson; Elizabeth Chiao; Albert C. Koong; Ernest Hawk; et al. (Journal of Cancer Education, 2024)
Providing safe and informed healthcare for sexual and gender minority (SGM) individuals with cancer is stymied by the lack of sexual orientation and gender identity (SOGI) data reliably available in health records and by insufficient training for staff. Approaches that support institutional learning, especially around sensitive topics, are essential for hospitals seeking to improve practices impacting patient safety and research. We engineered annual institutional retreats to identify and unify stakeholders, promote awareness of gaps and needs, identify initiatives, minimize redundant projects, and coordinate efforts that promote improvements in SGM cancer care, education, and research. The 2022 and 2023 retreats employed a 4-h hybrid format allowing virtual and in-person engagement. Retreat organizers facilitated small-group discussions for brainstorming among participants. We performed descriptive statistics from retreat evaluations. The retreats engaged 104 attendees from distinct departments and roles. Participants expressed robust satisfaction, commending the retreat organization and content quality. Notably, the first retreat yielded leadership endorsement and funding for a Quality Improvement pilot to standardize SOGI data collection and clinical staff training. The second retreat provided a platform for updates on focused efforts across the institution and for receiving direction regarding national best practices for SGM care and research. We report the processes and outcomes of institution-wide retreats, which served as a platform for identifying gaps in organizational healthcare practices and research for SGM individuals with cancer. The strategies described herein may be readily scaled at other cancer hospitals seeking to learn and enact system-wide practice changes that support the needs of SGM patients and families.

Virus ecology and 7‐year temporal dynamics across a permafrost thaw gradient - Christine L. Sun; Akbar Adjie Pratama; Maria Consuelo Gazitúa; Dylan Cronin; Bridget B. McGivern; James M. Wainaina; Dean R. Vik; Ahmed A. Zayed; Benjamin Bolduc; Kelly C. Wrighton; Virginia I. Rich; Matthew B. Sullivan (Environmental Microbiology, 2024)
Soil microorganisms are pivotal in the global carbon cycle, but the viruses that affect them and their impact on ecosystems are less understood. In this study, we explored the diversity, dynamics, and ecology of soil viruses through 379 metagenomes collected annually from 2010 to 2017. These samples spanned the seasonally thawed active layer of a permafrost thaw gradient, which included palsa, bog, and fen habitats. We identified 5051 virus operational taxonomic units (vOTUs), doubling the known viruses for this site. These vOTUs were largely ephemeral within habitats, suggesting a turnover at the vOTU level from year to year. While the diversity varied by thaw stage and depth‐related patterns were specific to each habitat, the virus communities did not significantly change over time. The abundance ratios of virus to host at the phylum level did not show consistent trends across the thaw gradient, depth, or time. To assess potential ecosystem impacts, we predicted hosts in silico and found viruses linked to microbial lineages involved in the carbon cycle, such as methanotrophy and methanogenesis. This included the identification of viruses of Candidatus Methanoflorens, a significant global methane contributor. We also detected a variety of potential auxiliary metabolic genes, including 24 carbon‐degrading glycoside hydrolases, six of which are uniquely terrestrial. In conclusion, these long‐term observations enhance our understanding of soil viruses in the context of climate‐relevant processes and provide opportunities to explore their role in terrestrial carbon cycling.

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Heterozygous loss-of-function variants in DOCK4 cause neurodevelopmental delay and microcephaly - Charlotte Herbst; Viktoria Bothe; Meret Wegler; Susanne Axer-Schaefer; Séverine Audebert-Bellanger; Jozef Gecz; Benjamin Cogne; Hagit Baris Feldman; Anselm H. C. Horn; Anna C. E. Hurst; Melissa A. Kelly; Michael C. Kruer; et al. (Human Genetics, 2024)
Neurons form the basic anatomical and functional structure of the nervous system, and defects in neuronal differentiation or formation of neurites are associated with various psychiatric and neurodevelopmental disorders. Dynamic changes in the cytoskeleton are essential for this process, which is, inter alia, controlled by the dedicator of cytokinesis 4 ( DOCK4 ) through the activation of RAC1 . Here, we clinically describe 7 individuals (6 males and one female) with variants in DOCK4 and overlapping phenotype of mild to severe global developmental delay. Additional symptoms include coordination or gait abnormalities, microcephaly, nonspecific brain malformations, hypotonia and seizures. Four individuals carry missense variants (three of them detected de novo) and three individuals carry null variants (two of them maternally inherited). Molecular modeling of the heterozygous missense variants suggests that the majority of them affect the globular structure of DOCK4. In vitro functional expression studies in transfected Neuro-2A cells showed that all missense variants impaired neurite outgrowth. Furthermore, Dock4 knockout Neuro-2A cells also exhibited defects in promoting neurite outgrowth. Our results, including clinical, molecular and functional data, suggest that loss-of-function variants in DOCK4 probable cause a variable spectrum of a novel neurodevelopmental disorder with microcephaly.

Recommendations for Method Development and Validation of qPCR and dPCR Assays in Support of Cell and Gene Therapy Drug Development - Amanda Hays; Mark Wissel; Kelly Colletti; Russell Soon; Mitra Azadeh; Justin Smith; Rajitha Doddareddy; Melanie Chalfant; Wendy Adamowicz; Swarna Suba Ramaswamy; Sanjay L. Dholakiya; Sebastian Guelman; et al. (The AAPS Journal, 2024)
The emerging use of qPCR and dPCR in regulated bioanalysis and absence of regulatory guidance on assay validations for these platforms has resulted in discussions on lack of harmonization on assay design and appropriate acceptance criteria for these assays. Both qPCR and dPCR are extensively used to answer bioanalytical questions for novel modalities such as cell and gene therapies. Following cross-industry conversations on the lack of information and guidelines for these assays, an American Association of Pharmaceutical Scientists working group was formed to address these gaps by bringing together 37 industry experts from 24 organizations to discuss best practices to gain a better understanding in the industry and facilitate filings to health authorities. Herein, this team provides considerations on assay design, development, and validation testing for PCR assays that are used in cell and gene therapies including (1) biodistribution; (2) transgene expression; (3) viral shedding; (4) and persistence or cellular kinetics of cell therapies. Graphical Abstract

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Hurricane Effects on Seagrass and Associated Nekton Communities in the Northern Gulf of Mexico - Kelly M. Correia; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Darnell; M. Zachary Darnell; Bradley T. Furman; Margaret O. Hall; Christian T. Hayes; Charles W. Martin; Ashley McDonald; Delbert L. Smee (Estuaries and Coasts, 2024)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Bullous keratopathy in a dwarf rabbit (Oryctolagus cuniculus domesticus) - William Irving; Cameron Whittaker; Kelly Caruso; Benjamin Reynolds; Paul McCarthy; Jeff Smith (Journal of Exotic Pet Medicine, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Small-scale oxygen distribution patterns in a coral reef - Adam S. Candy; Shannara K. Taylor Parkins; Fleur C. Van Duyl; Benjamin Mueller; Milou G. I. Arts; Will Barnes; Marie Carstensen; Yun J. H. Scholten; Yusuf C. El-Khaled; Christian Wild; Linda Wegley Kelly; Craig E. Nelson; et al. (Frontiers in Marine Science, 2023)
One mechanism giving fleshy algae a competitive advantage over corals during reef degradation is algal-induced and microbially-mediated hypoxia (typically less than 69.5 µmol oxygen L −1 ). During hypoxic conditions oxygen availability becomes insufficient to sustain aerobic respiration in most metazoans. Algae are more tolerant of low oxygen conditions and may outcompete corals weakened by hypoxia. A key question on the ecological importance of this mechanism remains unanswered: How extensive are local hypoxic zones in highly turbulent aquatic environments, continuously flushed by currents and wave surge? To better understand the concert of biological, chemical, and physical factors that determine the abundance and distribution of oxygen in this environment, we combined 3D imagery, flow measurements, macro- and micro-organismal abundance estimates, and experimentally determined biogenic oxygen and carbon fluxes as input values for a 3D bio-physical model. The model was first developed and verified for controlled flume experiments containing coral and algal colonies in direct interaction. We then developed a three-dimensional numerical model of an existing coral reef plot off the coast of Curaçao where oxygen concentrations for comparison were collected in a small-scale grid using fiberoptic oxygen optodes. Oxygen distribution patterns given by the model were a good predictor for in situ concentrations and indicate widespread localized differences exceeding 50 µmol L -1 over distances less than a decimeter. This suggests that small-scale hypoxic zones can persist for an extended period of time in the turbulent environment of a wave- and surge- exposed coral reef. This work highlights how the combination of three-dimensional imagery, biogenic fluxes, and fluid dynamic modeling can provide a powerful tool to illustrate and predict the distribution of analytes (e.g., oxygen or other bioactive substances) in a highly complex system.

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Epidemiology and economic impact of disease-related losses on commercial catfish farms: A seven-year case study from Alabama, USA - Hisham A. Abdelrahman; William G. Hemstreet; Luke A. Roy; Terrill R. Hanson; Benjamin H. Beck; Anita M. Kelly (Aquaculture, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Feces consumption by nominally herbivorous fishes in the Caribbean: an underappreciated source of nutrients? - Hannah S. Rempel; Abigail K. Siebert; Jacey C. Van Wert; Kelly N. Bodwin; Benjamin I. Ruttenberg (Coral Reefs, 2022)
Parrotfishes and surgeonfishes are major Caribbean herbivores that primarily graze reef algae and thereby play an important functional role in indirectly promoting coral recruitment and growth. Yet, an emerging body of research suggests that these nominal herbivores graze on a diverse array of other food sources and researchers have questioned whether they may target more nutrient-dense foods growing within or upon algae, such as cyanobacteria. In this study, we investigated the species-specific foraging rates of parrotfishes and surgeonfishes on Brown Chromis ( Chromis multilineata) fecal pellets compared to other major dietary items. We found that almost 85% of observed fecal pellets were ingested by fishes and that over 90% of ingested fecal pellets were consumed by parrotfishes and surgeonfishes alone. While there were species-specific differences in the levels of feces consumption (coprophagy), we found that all three surgeonfishes (Acanthurus chirurgus, A. coeruleus, and A. tractus) and six of the nine of parrotfish species surveyed (Scarus coeruleus, S. iseri, S. taeniopterus, S. vetula, Sparisoma aurofrenatum, and S. viride) consumed C. multilineata feces. To better understand the nutritional value of this behavior, we analyzed the composition of proteins, lipids, carbohydrates, total calories, and micronutrients in C. multilineata fecal pellets and compared these to published values for other food sources targeted by these fishes. Our findings suggest that these fecal pellets may have higher values of proteins, carbohydrates, total calories, and important micronutrients, such as phosphorus, compared to various macroalgae and the epilithic algae matrix, though comparable or lower values compared to cyanobacteria. To our knowledge, this is the first study to document coprophagy by tropical herbivorous fishes in the Caribbean region. This research advances our understanding of the foraging ecology of nominally herbivorous fishes and highlights the importance of fish feces as a nutritional resource on coral reefs. Graphical abstract

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

Environmental Drivers of Seagrass-Associated Nekton Abundance Across the Northern Gulf of Mexico - Benjamin A. Belgrad; Kelly M. Correia; Kelly M. Darnell; M. Zachary Darnell; Christian T. Hayes; Margaret O. Hall; Bradley T. Furman; Charles W. Martin; Delbert L. Smee (Estuaries and Coasts, 2021)

Occurrence of environmental contaminants (pesticides, herbicides, PAHs) in Australian/Queensland Apis mellifera honey - Natasha L. Hungerford; Mary T. Fletcher; Heng Hang Tsai; Darina Hnatko; Lorinda J. Swann; Cassandra L. Kelly; Shalona R. Anuj; Ujang Tinggi; Dennis C. Webber; Stephen T. Were; Benjamin L. L. Tan (Food Additives & Contaminants Part B-Surveillance, 2021)

Three-Dimensional Molecular Cartography of the Caribbean Reef-Building Coral Orbicella faveolata - Mark Little; Emma E. George; Milou G. I. Arts; Jade Shivak; Sean Benler; Joel Huckeba; Zachary A. Quinlan; Vittorio Boscaro; Benjamin Mueller; Ana Georgina Cobián Güemes; Maria Isabel Rojas; Brandie White; et al. (Frontiers in Marine Science, 2021)
All organisms host a diversity of associated viruses, bacteria, and protists, collectively defined as the holobiont. While scientific advancements have enhanced the understanding of the functional roles played by various components of the holobiont, there is a growing need to integrate multiple types of molecular data into spatially and temporally resolved frameworks. To that end, we mapped 16S and 18S rDNA metabarcoding, metatranscriptomics, and metabolomic data onto three-dimensional reconstructions of coral colonies to examine microbial diversity, microbial gene expression, and biochemistry on two colonies of the ecologically important, reef-building coral, Orbicella faveolata and their competitors (i.e., adjacent organisms interacting with the corals: fleshy algae, turf algae, hydrozoans, and other corals). Overall, no statistically significant spatial patterns were observed among the samples for any of the data types; instead, strong signatures of the macroorganismal hosts (e.g., coral, algae, hydrozoa) were detected, in the microbiome, the transcriptome, and the metabolome. The 16S rDNA analysis demonstrated higher abundance of Firmicutes in the coral microbiome than in its competitors. A single bacterial amplicon sequence variant from the genus Clostridium was found exclusively in all O. faveolata samples. In contrast to microbial taxa, a portion of the functionally annotated bacterial RNA transcripts (6.86%) and metabolites (1.95%) were ubiquitous in all coral and competitor samples. Machine learning analysis of microbial transcripts revealed elevated T7-like cyanophage-encoded photosystem II transcripts in O. faveolata samples, while sequences involved in bacterial cell division were elevated in turf algal and interface samples. Similar analysis of metabolites revealed that bacterial-produced antimicrobial and antifungal compounds were highly enriched in coral samples. This study provides insight into the spatial and biological patterning of the coral microbiome, transcriptome, and metabolome.

Spatial Management Measures Alter Vessel Behavior in the Aleutian Archipelago - Benjamin K. Sullender; Kelly Kapsar; Aaron Poe; Martin Robards (Frontiers in Marine Science, 2021)
The Aleutian Archipelago and surrounding waters have enormous ecological, cultural, and commercial significance. As one of the shortest routes between North American and Asian ports, the North Pacific Great Circle Route, which crosses through the Aleutian Archipelago, is traveled by thousands of large cargo ships and tanker vessels every year. To reduce maritime risks and enhance navigational safety, the International Maritime Organization built upon earlier offshore routing efforts by designating five Areas To Be Avoided (ATBAs) in the Aleutian Islands in 2016. The ATBAs are designed to keep large vessels at least 50 nautical miles (93 km) from shore unless calling at a local port or transiting an authorized pass between islands. However, very few studies have examined the effectiveness of ATBAs as a mechanism for changing vessel behavior and thereby reducing the ecological impacts of maritime commerce. In this study, we use 4 years of satellite-based vessel tracking data to assess the effectiveness of the Aleutian ATBAs since their implementation in 2016. We determined whether vessels transiting the North Pacific Great Circle Route changed behavior after ATBA implementation, both in terms of overall route selection and in terms of compliance with each ATBA boundary. We found a total of 2,252 unique tankers and cargo vessels >400 gross tons transited the study region, completing a total of 8,794 voyages. To quantify routing changes of individual vessels, we analyzed the 767 vessels that transited the study region both before and after implementation. The percentage of voyages transiting through the boundaries of what would become ATBAs decreased from 76.3% in 2014–2015 (prior to ATBA designation) to 11.8% in 2016–2017 (after implementation). All five Aleutian ATBAs had significant increases in compliance, with the West ATBA showing the most dramatic increase, from 32.1% to 95.0%. We discuss the framework for ATBA enforcement and highlight the value of local institutional capacity for real-time monitoring. Overall, our results indicate that ATBAs represent a viable strategy for risk mitigation in sensitive ecological areas and that through monitoring, spatial protections influence vessel route decisions on multiple spatial scales.

Impacts of parrotfish predation on a major reef-building coral: quantifying healing rates and thresholds of coral recovery - Hannah S. Rempel; Kelly N. Bodwin; Benjamin I. Ruttenberg (Coral Reefs, 2020)

Effects of terrestrial transport corridors and associated landscape context on invasion by forest plants - Samuel F. Ward; Benjamin S. Taylor; Kelly-Ann Dixon Hamil; Kurt H. Riitters; Songlin Fei (Biological Invasions, 2020)

Effects of Saltwater Pulses on Soil Microbial Enzymes and Organic Matter Breakdown in Freshwater and Brackish Coastal Wetlands - Shelby Servais; John S. Kominoski; Carlos Coronado-Molina; Laura Bauman; Stephen E. Davis; Evelyn E. Gaiser; Stephen Kelly; Christopher Madden; Viviana Mazzei; David Rudnik; Fabiola Santamaria; Fred H. Sklar; et al. (Estuaries and Coasts, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Determinants of sulphur chemolithoautotrophy in the extremely thermoacidophilic Sulfolobales - Benjamin M. Zeldes; Andrew J. Loder; James A. Counts; Mashkurul Haque; Karl A. Widney; Lisa M. Keller; Sonja‐Verena Albers; Robert M. Kelly (Environmental Microbiology, 2019)
Summary Species in the archaeal order Sulfolobales thrive in hot acid and exhibit remarkable metabolic diversity. Some species are chemolithoautotrophic, obtaining energy through the oxidation of inorganic substrates, sulphur in particular, and acquiring carbon through the 3‐hydroxypropionate/4‐hydroxybutyrate (3‐HP/4‐HB) CO 2 ‐fixation cycle. The current model for sulphur oxidation in the Sulfolobales is based on the biochemical analysis of specific proteins from Acidianus ambivalens , including sulphur oxygenase reductase (SOR) that disproportionates S° into H 2 S and sulphite (SO 3 2− ). Initial studies indicated SOR catalyses the essential first step in oxidation of elemental sulphur, but an ancillary role for SOR as a ‘recycle’ enzyme has also been proposed. Here, heterologous expression of both SOR and membrane‐bound thiosulphate‐quinone oxidoreductase (TQO) from Sulfolobus tokodaii ‘restored’ sulphur oxidation capacity in Sulfolobus acidocaldarius DSM639, but not autotrophy, although earlier reports indicate this strain was once capable of chemolithoautotrophy. Comparative transcriptomic analyses of Acidianus brierleyi , a chemolithoautotrophic sulphur oxidizer, and S. acidocaldarius DSM639 showed that while both share a strong transcriptional response to elemental sulphur, S. acidocaldarius DSM639 failed to upregulate key 3‐HP/4‐HB cycle genes used by A. brierleyi to drive chemolithoautotrophy. Thus, the inability for S. acidocaldarius DSM639 to grow chemolithoautotrophically may be rooted more in gene regulation than the biochemical capacity.

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Holding steady: Little change in intensity or timing of bird migration over the Gulf of Mexico - Kyle G. Horton; Benjamin M. Van Doren; Frank A. La Sorte; Emily B. Cohen; Hannah L. Clipp; Jeffrey J. Buler; Daniel Fink; Jeffrey F. Kelly; Andrew Farnsworth (Global Change Biology, 2019)
Quantifying the timing and intensity of migratory movements is imperative for understanding impacts of changing landscapes and climates on migratory bird populations. Billions of birds migrate in the Western Hemisphere, but accurately estimating the population size of one migratory species, let alone hundreds, presents numerous obstacles. Here, we quantify the timing, intensity, and distribution of bird migration through one of the largest migration corridors in the Western Hemisphere, the Gulf of Mexico (the Gulf). We further assess whether there have been changes in migration timing or intensity through the Gulf. To achieve this, we integrate citizen science (eBird) observations with 21 years of weather surveillance radar data (1995–2015). We predicted no change in migration timing and a decline in migration intensity across the time series. We estimate that an average of 2.1 billion birds pass through this region each spring en route to Nearctic breeding grounds. Annually, half of these individuals pass through the region in just 18 days, between April 19 and May 7. The western region of the Gulf showed a mean rate of passage 5.4 times higher than the central and eastern regions. We did not detect an overall change in the annual numbers of migrants (2007–2015) or the annual timing of peak migration (1995–2015). However, we found that the earliest seasonal movements through the region occurred significantly earlier over time (1.6 days decade −1 ). Additionally, body mass and migration distance explained the magnitude of phenological changes, with the most rapid advances occurring with an assemblage of larger‐bodied shorter‐distance migrants. Our results provide baseline information that can be used to advance our understanding of the developing implications of climate change, urbanization, and energy development for migratory bird populations in North America.

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Navigating north: how body mass and winds shape avian flight behaviours across a North American migratory flyway - Kyle G. Horton; Benjamin M. Van Doren; Frank A. La Sorte; Daniel Fink; Daniel Sheldon; Andrew Farnsworth; Jeffrey F. Kelly (Ecology Letters, 2018)
The migratory patterns of birds have been the focus of ecologists for millennia. What behavioural traits underlie these remarkably consistent movements? Addressing this question is central to advancing our understanding of migratory flight strategies and requires the integration of information across levels of biological organisation, e.g. species to communities. Here, we combine species‐specific observations from the eB ird citizen‐science database with observations aggregated from weather surveillance radars during spring migration in central North America. Our results confirm a core prediction of migration theory at an unprecedented national scale: body mass predicts variation in flight strategies across latitudes, with larger‐bodied species flying faster and compensating more for wind drift. We also find evidence that migrants travelling northward earlier in the spring increasingly compensate for wind drift at higher latitudes. This integration of information across biological scales provides new insight into patterns and determinants of broad‐scale flight strategies of migratory birds.

Correction to: Consequences of the physical nature of the parent material for pedogenesis, nutrient availability, and succession in temperate rainforests - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant and Soil, 2018)

Consequences of the physical nature of the parent material for pedogenesis, nutrient availability, and succession in temperate rainforests - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant and Soil, 2018)

Early burst in body size evolution is uncoupled from species diversification in diving beetles (Dytiscidae) - Aurélie Désamoré; Benjamin Laenen; Kelly B. Miller; Johannes Bergsten (Molecular Ecology, 2018)
Changes in morphology are often thought to be linked to changes in species diversification, which is expected to leave a signal of early burst ( EB ) in phenotypic traits. However, such signal is rarely recovered in empirical phylogenies, even for groups with well‐known adaptive radiation. Using a comprehensive phylogenetic approach in Dytiscidae, which harbours ~4,300 species with as much as 50‐fold variation in body size among them, we ask whether pattern of species diversification correlates with morphological evolution. Additionally, we test whether the large variation in body size is linked to habitat preference and whether the latter influences species turnover. We found, in sharp contrast to most animal groups, that Dytiscidae body size evolution follows an early‐burst model with subsequent high phylogenetic conservatism. However, we found no evidence for associated shifts in species diversification, which point to an uncoupled evolution of morphology and species diversification. We recovered the ancestral habitat of Dytiscidae as lentic (standing water), with many transitions to lotic habitat (running water) that are concomitant to a decrease in body size. Finally, we found no evidence for difference in net diversification rates between habitats nor difference in turnover in lentic and lotic species. This result, together with recent findings in dragonflies, contrasts with some theoretical expectations of the habitat stability hypothesis. Thus, a thorough reassessment of the impact of dispersal, gene flow and range size on the speciation process is needed to fully encompass the evolutionary consequences of the lentic–lotic divide for freshwater fauna.

Central nervous system-penetrating antiretrovirals impair energetic reserve in striatal nerve terminals - Kelly L. Stauch; Katy Emanuel; Benjamin G. Lamberty; Brenda Morsey; Howard S. Fox (Journal of NeuroVirology, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Plasticity in nitrogen uptake among plant species with contrasting nutrient acquisition strategies in a tropical forest - Kelly M. Andersen; Jordan R. Mayor; Benjamin L. Turner (Ecology, 2017)
Nitrogen (N) availability influences the productivity and distribution of plants in tropical montane forests. Strategies to acquire soil N, such as direct uptake of organic compounds or associations with root symbionts to enhance N acquisition in exchange for carbon (C), may facilitate plant species coexistence and ecosystem N retention. Alternatively, rapid microbial turnover of soil N forms in tropical soils might promote flexible plant N‐uptake strategies and mediate species coexistence. We tested whether sympatric plant species with different root symbiont associations, and therefore potentially different nutrient acquisition strategies, partition chemical forms of N or show plasticity in N uptake in a tropical pre‐montane forest in Panama. We traced the movement of three 15 N forms into soil pools, microbes, and seedlings of eleven species differing in root traits. Seedlings were grown in a split‐plot field transplant experiment, with plots receiving equimolar mixtures of ammonium, nitrate, and glycine, with one form isotopically labeled in each block. After 48 h, more 15 N was recovered in microbes than in plants, while all pools (extractable organic and inorganic N, microbial biomass, and leaves) contained greater amounts of 15 N from nitrate than from ammonium or glycine. Furthermore, 13 C from dual‐labeled glycine was not recovered in the leaves of any seedling, suggesting the studied species do not directly take up organic N or transform organic N prior to translocation to leaves. Nitrogen uptake differed by root symbiont group only for nitrate, with greater 15 N recovery in plants with arbuscular mycorrhizal (AM) associations or proteoid roots compared to orchids. Some root trait groups differed in 15 N recovery among N forms, with greater nitrate uptake than ammonium or glycine by AM‐associated and N 2 ‐fixing plants. However, only five of eleven species showed differences in uptake among N forms. These results indicate flexibility in uptake of N forms in tropical plants across root trait groups, with only a few species displaying weak preferences for a specific N form.

Seedling performance trade‐offs influencing habitat filtering along a soil nutrient gradient in a tropical forest - Kelly M. Andersen; Benjamin L. Turner; James W. Dalling (Ecology, 2014)
Recent studies have provided evidence that trade‐offs in biomass allocation, resource‐use efficiency, and anti‐herbivore defense influence seedling performance and distribution across soil types. Our previous research suggested that soil nutrient availability acted as a filter for understory palm community assembly and species coexistence in a lower montane forest in western Panama. Here, we experimentally tested three potential mechanisms that could be driving this filtering of palm communities along a soil nutrient gradient. We examined seedling performance of 13 understory palm taxa with differing distribution patterns transplanted to five sites, where they were both exposed to and protected from herbivores. We found the strongest evidence for habitat filtering at the lowest‐nutrient site, where seedlings of locally occurring species had significant performance advantages over those of locally absent species, regardless of protection from herbivores. When transplanted to the lowest‐nutrient site, seedlings of naturally occurring species maintained high above‐ to belowground biomass ratios, maximized photosynthetic nitrogen‐use efficiency, and minimized leaf area loss to herbivores and pathogens. Species from low‐fertility sites were therefore able to maintain higher survival and relative growth rates (RGR) at the lowest‐nutrient site than species from more fertile sites. Similar patterns were found for a high‐nutrient site, where naturally occurring species had higher RGR compared to species from lower‐fertility sites. However, the functional traits associated with the differences in performance at high‐nutrient sites were less clear, perhaps due to increased light limitation in the understory of these sites. At higher‐nutrient sites, protection from herbivores significantly reduced leaf area damage and mortality rates in seedlings, particularly for naturally occurring species. Overall, morphological and physiological traits were more strongly coupled with soil nutrient availability than were leaf damage or seedling performance across the sites. Nonetheless, the coordination of all three trade‐offs was related to the strongest performance advantage and, therefore, ecological filtering along the soil nutrient gradient in this lower montane forest.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Misperceptions of ovarian cancer risk in women at increased risk for hereditary ovarian cancer - Bettina Meiser; Melanie A. Price; Phyllis N. Butow; Belinda Rahman; Kathy Tucker; Benjamin Cheah; Adrian Bickerstaffe; John Hopper; Kelly-Anne Phillips (Familial Cancer, 2014)

The impact of high-intensity intermittent exercise on resting metabolic rate in healthy males - Benjamin Kelly; James A. King; Jonas Goerlach; Myra A. Nimmo (European Journal of Applied Physiology, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Hydraulic responses to extreme drought conditions in three co-dominant tree species in shallow soil over bedrock - Kelly R. Kukowski; Susanne Schwinning; Benjamin F. Schwartz (Oecologia, 2013)

Patterns of tree community composition along a coastal dune chronosequence in lowland temperate rain forest in New Zealand - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant Ecology, 2012)

Trait-based community assembly of understory palms along a soil nutrient gradient in a lower montane tropical forest - Kelly M. Andersen; Maria Jose Endara; Benjamin L. Turner; James W. Dalling (Oecologia, 2012)

Characterization of full-length MHC class II sequences in Indonesian and Vietnamese cynomolgus macaques - Hannah M. Creager; Ericka A. Becker; Kelly K. Sandman; Julie A. Karl; Simon M. Lank; Benjamin N. Bimber; Roger W. Wiseman; Austin L Hughes; Shelby L. O’Connor; David H. O’Connor (Immunogenetics, 2011)

Effect of resistance training during hemodialysis on circulating cytokines: a randomized controlled trial - Birinder Singh Bobby Cheema; Haifa Abas; Benjamin C. F. Smith; Anthony J. O’Sullivan; Maria Chan; Aditi Patwardhan; John Kelly; Adrian Gillin; Glen Pang; Brad Lloyd; Klaus Berger; Bernhard T. Baune; et al. (European Journal of Applied Physiology, 2011)

Combining Ecological Classification Systems and Conservation Filters Could Facilitate the Integration of Wildlife and Forest Management - Eric K. Zenner; JeriLynn E. Peck; Kristen Brubaker; Benjamin Gamble; Carrie Gilbert; Daniel Heggenstaller; Jeanne Hickey; Kelly Sitch; Robbie Withington (Journal of Forestry, 2010)
Ecosystem management demands simultaneous consideration and integration of ecosystem services in monitoring, planning, and management activities, but specialization has led to independently developed traditions in wildlife biology and management and forestry. We drew on the literature to explore the use of filters in wildlife conservation and ecological classification systems in forest management and to ask the question, “Can combining these tools improve our integration of wildlife and forest management?” Although each tool has been successfully applied independently, relatively few examples still exist for their combined use. We conclude that this approach has potential for enhancing research, monitoring, and management in areas beyond wildlife management, including forest health.

Soil‐based habitat partitioning in understorey palms in lower montane tropical forests - Kelly M. Andersen; Benjamin L. Turner; James W. Dalling (Journal of Biogeography, 2010)
Aim Dispersal assembly and niche assembly are two competing theories proposed to explain the maintenance of species diversity in tropical forests. Dispersal theory emphasizes the role of chance colonization events and distance‐limited seed dispersal in explaining species abundance and distribution, whereas niche theory emphasizes differences among species in requirements for potentially limiting resources. Species distribution patterns in tropical forests often correlate with geology and topography, but tests of the relative importance of dispersal and niche partitioning have been hampered by an inadequate characterization of resource availability. The aim of this study was to explore how soil chemical and physical properties, climate, and geographic distance affect understorey palm communities in lower montane forests. Location Fortuna Forest Reserve, Chiriqui Province, and Palo Seco Forest Reserve, Bocas del Toro Province, in western Panama. Methods Understorey palms and soil nutrient concentrations were surveyed within 10 sites on different soil types across a 13‐km transect. Variation in palm community composition was examined in relation to spatial and environmental variables. Results The 25 understorey palm species recorded in the study were non‐randomly distributed among forests differing in soil nutrient availability. In support of dispersal theory, floristic similarity decreased predictably with increasing geographic distance. However, environmental and soil variables were also correlated with geographic distance. Floristic similarity was also highly associated with a subset of environmental variables. Variation in palm community similarity was most strongly correlated with inorganic nitrogen availability and cation concentration. A subset of soil variables had a stronger relationship with floristic similarity when geographic distance was controlled for than did geographic distance when differences in soils were controlled for. Main conclusions Both dispersal and niche processes affect palm species distribution patterns. Although spatially limited dispersal may influence species distribution patterns, soil‐based habitat associations, particularly with respect to soil nitrogen, cation availability and aluminium concentrations, remain important factors influencing palm community composition at the mesoscale level in this tropical montane forest.

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Host genetic polymorphisms in human immunodeficiency virus–related neurologic disease - Ramon Diaz-Arrastia; Yunhua Gong; Cynthia J Kelly; Benjamin B Gelman (Journal of NeuroVirology, 2004)

Pollinator behaviour, not increased resources, boosts seed set on forest edges in a New Zealand Loranthaceous mistletoe - Benjamin R. Montgomery; Dave Kelly; Alastair W. Robertson; Jenny J. Ladley (New Zealand Journal of Botany, 2003)
The endemic New Zealand mistletoe Peraxilla tetrapetala (Loranthaceae) has previously been shown to be pollinator limited, and to experience higher fruit set in increasingly fragmented habitats, but the mechanism for higher fruit set on edges has not been studied. Edges could affect plant resources (through higher light) and/or pollinator behaviour. This study measures the degree to which pollination and resource limitation affect female reproductive success along a gradient of increasing exposure to the forest edge. Forty‐two plants in pairs at varying distances from the forest edge were selected from within two Nothofagus forest fragments in the 1999/2000 season; and on one plant in each pair, all ripe undamaged flowers were hand‐pollinated. Light levels and the degree of edge exposure were measured for each plant, and path analysis was used to determine the relationship of these variables to proportion fruit set. In agreement with previous studies, unmanipulated plants were found to be strongly pollen limited, especially in shady locations. However, on plants receiving hand‐pollination, fruit set was uniformly high and was unaffected by edge exposure or light levels. Direct observation of flower visitation rates by birds in the 2000/01 season showed that edge flowers were visited twice as often as interior flowers. These results show that the higher fruit set on edges is due to visitation patterns of pollinators, and not due to greater resource availability on edges. This improved pollination on edges may help to buffer this declining plant against local extinction.